2014
DOI: 10.5414/cn108053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fabry’s disease within hemodialysis patients in Spain

Abstract: This study reveals the need for screening for FD in all patients under hemodialysis for unknown causes and indicates that the incidence and prevalence of FD are underestimated so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Since they are already in dialysis, histological confirmation of Fabry nephropathy is not an option, and ESRD itself may explain most coexistent cardiac or central nervous system involvements. In this regard, the prevalence of the R118C GLA variant (5 of 3,650, 0.14%) in Spanish hemodialysis patients was reported to be similar to the prevalence found in Portuguese healthy subjects (1 of 696; 0.14%), and most patients with the R118C variant do not have features of FD [10,11]. Thus, it is unlikely that Fabry nephropathy explains the ESRD of R118C patients identified in the Spanish hemodialysis screening [10,12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Since they are already in dialysis, histological confirmation of Fabry nephropathy is not an option, and ESRD itself may explain most coexistent cardiac or central nervous system involvements. In this regard, the prevalence of the R118C GLA variant (5 of 3,650, 0.14%) in Spanish hemodialysis patients was reported to be similar to the prevalence found in Portuguese healthy subjects (1 of 696; 0.14%), and most patients with the R118C variant do not have features of FD [10,11]. Thus, it is unlikely that Fabry nephropathy explains the ESRD of R118C patients identified in the Spanish hemodialysis screening [10,12].…”
Section: Introductionmentioning
confidence: 83%
“…In this regard, the prevalence of the R118C GLA variant (5 of 3,650, 0.14%) in Spanish hemodialysis patients was reported to be similar to the prevalence found in Portuguese healthy subjects (1 of 696; 0.14%), and most patients with the R118C variant do not have features of FD [10,11]. Thus, it is unlikely that Fabry nephropathy explains the ESRD of R118C patients identified in the Spanish hemodialysis screening [10,12]. It is thus critical to assess the pathogenicity of any novel mutation found in hemodialysis screening, given the impact of prescribing high-cost ERT on patients and society.…”
Section: Introductionmentioning
confidence: 89%
“…Detection of those index cases led us to locate additional undiagnosed patients. The prevalence of FD in hemodialysis patients has been studied extensively [24,[25][26][27][28]. However, there are few studies conducted on patients who had undergone kidney Tx [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of early diagnosis to begin treatment as early as possible has been reported [17, 25-28]. Zarate and Hopkin (2008) reported that there is no known ethnic predisposition for FD but that there are some regional pockets with higher FD incidence, including Nova Scotia in Canada and Virginia in the USA [4].…”
Section: Discussionmentioning
confidence: 99%